1979
DOI: 10.1007/bf02671785
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐water interactions and functional properties

Abstract: Hydration or rehydration is the first and perhaps most critical step in imparting desired functional properties to proteins in a food system. Water that interacts with the protein molecule exhibits different properties from those of "free" water. The types of water in protein-food systems are described in terms of structural, monolayers, unfreezable, hydrophobic hydration, imbibition or capillary condensation, and hydrodynamic hydration water. Protein functional properties such as swelling, solubility, gelatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0
19

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(120 citation statements)
references
References 48 publications
3
98
0
19
Order By: Relevance
“…The pH, ionic strength, temperature, heating rate, protein concentrations and other factors influenced the WHC (Camou, Sebranek, & Olson, 1989;Chou & Morr, 1979;Huff-Lonergan & Lonergan, 2005;Kristinsson & Hultin, 2003;Westphalen et al, 2005;Yongsawatdigul & Park, 1999). Westphalen et al (2005) found a direct linear relationship between WHC and pH, which was consistent with Offer and Trinick's findings (Offer & Trinick, 1983), and attributed the relationship to the possibility of increased protein-water hydrogen bonding at high pH values.…”
Section: Whc Of the Heat-induced Myofibrillar Gel At 65°csupporting
confidence: 75%
See 1 more Smart Citation
“…The pH, ionic strength, temperature, heating rate, protein concentrations and other factors influenced the WHC (Camou, Sebranek, & Olson, 1989;Chou & Morr, 1979;Huff-Lonergan & Lonergan, 2005;Kristinsson & Hultin, 2003;Westphalen et al, 2005;Yongsawatdigul & Park, 1999). Westphalen et al (2005) found a direct linear relationship between WHC and pH, which was consistent with Offer and Trinick's findings (Offer & Trinick, 1983), and attributed the relationship to the possibility of increased protein-water hydrogen bonding at high pH values.…”
Section: Whc Of the Heat-induced Myofibrillar Gel At 65°csupporting
confidence: 75%
“…Damodaran (2007) studied water in proteins and found that -CO-and -NH became positive and negative polarization centers, respectively, forming multilayer water systems in polypeptide chains of denatured proteins. As the temperature decreased, free water would be entrapped by the structure partly due to hydrogen bonds between proteins (Chou & Morr, 1979;Damodaran, 2007).…”
Section: Whc Of the Heat-induced Myofibrillar Gel At 65°cmentioning
confidence: 99%
“…O volume de intumescimento (VI) foi maior enquanto que o índice de absorção de água (IAA) foi menor, provavelmente devido às mudanças na estrutura física ocorridas durante a hidrólise, pois o IAA depende da conformação molecular, tamanho das partículas, números de sítios de ligação das moléculas e força de centrifugação, enquanto o VI depende da densidade, porosidade e solubilidade (AUFFRET et al, 1994;CHOU;MORR, 1979). O VI da fração sólida da hidrólise da FAM foi menor que da FAO, provavelmente devido às diferenças ocorridas em consequência da diminui- A solubilidade proteica dos ingredientes obtidos após a hidrólise com a carboidrase também foi maior do que a solubilidade das fi bras alimentares (Tabela 2).…”
Section: Resultsunclassified
“…Influencia de la sal en la capacidad de retención de agua (CRA) en productos cárnicos La capacidad de retención de agua se define como la habilidad de la matriz tridimensional proteica del alimento para prevenir la pérdida de agua (Hermansson, 1986). Esta propiedad puede verse afectada por muchos parámetros propios de las proteínas, tales como: tamaño de poro, capilaridad, la carga de la matriz proteica (interacciones hidrofobicas, puentes de hidrogeno, puentes sulfuro-sulfuro, acidos, bases), asi como por las fuerzas de Van der waals (Chou et al, 1979;Hermansson, 1986;Lumry, 1973;Morr, 1989;Phillips, 1977).Adicionalmente a estos parámetros, el medio en el que se encuentre inmersa la matriz proteica puede afectar le CRA, debido a la fuerza iónica, las especies presentes, el pH, temperatura y el tiempo que se tarde en establecerse el equilibrio entre la proteína y el agua (De Wit, 7 1988;Kinsella, 1982;Mangino, 1984). Algunas sustancias, en particular de bajo peso molecular, como la lactosa o el cloruro de sodio, han sido reportadas como compuestos con un marcado efecto sobre la capacidad de retención de agua (Aljawad et al, 1988;Berlin et al, 1973;Hermansson et al, 1975;Ozimek et al, 1981).…”
unclassified
“…Influencia de la sal en la capacidad de retención de agua (CRA) en productos cárnicos La capacidad de retención de agua se define como la habilidad de la matriz tridimensional proteica del alimento para prevenir la pérdida de agua (Hermansson, 1986). Esta propiedad puede verse afectada por muchos parámetros propios de las proteínas, tales como: tamaño de poro, capilaridad, la carga de la matriz proteica (interacciones hidrofobicas, puentes de hidrogeno, puentes sulfuro-sulfuro, acidos, bases), asi como por las fuerzas de Van der waals (Chou et al, 1979;Hermansson, 1986;Lumry, 1973;Morr, 1989;Phillips, 1977).…”
unclassified